Current and future magnetic resonance technologies for assessing liver disease in clinical and experimental medicine - Bawden, Stephen; Scott, Robert; Authal, Guruprasad (Karger, 2017)
Background: In the past decades, a number of non-invasive methods have emerged for detecting and estimating liver fibrosis; these include both serum-based panels and imaging-based technology. Some of these methods are now being incorporated in clinical practice. However, the limitations of the current techniques include lack of organ specificity, sampling errors and limited ability to reflect the efficacy of interventions. Key Messages: Novel magnetic resonance (MR)-based techniques provide an opportunity to bring about further changes in the investigations and management of patients with liver diseases. Multimodal quantitative MR techniques enable the estimation of fat, iron accumulation, degree of liver injury/inflammation and fibrosis within the whole liver without the need for administering contrast agents. Architectural changes within the liver can be evaluated concurrently with portal haemodynamic changes allowing non-invasive assessment of portal hypertension and effects of interventions. A combination ultra-high field (7T) provides greater sensitivity with a potential to distinguish inflammation from fibrosis on imaging and determine specific types of fats (saturated vs. unsaturated) present within the liver using MR spectroscopy. 13 C MR spectroscopy can estimate glutathione flux and rate of beta oxidation in-vivo providing novel tools for experimental studies that evaluate the efficacy of interventions as well as underlying mechanisms. Conclusions: Translational research should focus on converting the potentials of these innovative methodologies into clinical applications for the benefit of patients.